2021
DOI: 10.1021/jacs.1c00399
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Potent Photooxidation Behavior of Catalytic Photoreductants

Abstract: We describe a photocatalytic system that reveals latent photooxidant behavior from one of the most reducing conventional photoredox catalysts, N-phenylphenothiazine (PTH). This aerobic photochemical reaction engages difficult to oxidize feedstocks, such as benzene, in C­(sp2)–N coupling reactions through direct oxidation. Mechanistic studies are consistent with activation of PTH via photooxidation and with Lewis acid cocatalysts scavenging inhibitors inextricably formed in this process.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 75 publications
(96 reference statements)
4
73
0
Order By: Relevance
“…Next, we recognized that nearly all photoredox catalysts, by design, undergo reversible redox events and many possess persistent radical anion congeners [6, 10, 75] . We questioned whether the structural features that render molecules effective as conventional photoredox catalysts would translate to the electron‐primed photoredox manifold [23, 76, 77] . Intriguingly, we found that electrolysis at the E red of several commonly employed photoredox catalysts Ru(bpy) 3 , [78] Ir(dF‐CF 3 ‐ppy) 2 (dtbpy), [78] and 4‐CzIPN [79] turned on photocatalytic activity in this challenging reduction [80] .…”
Section: Resultsmentioning
confidence: 99%
“…Next, we recognized that nearly all photoredox catalysts, by design, undergo reversible redox events and many possess persistent radical anion congeners [6, 10, 75] . We questioned whether the structural features that render molecules effective as conventional photoredox catalysts would translate to the electron‐primed photoredox manifold [23, 76, 77] . Intriguingly, we found that electrolysis at the E red of several commonly employed photoredox catalysts Ru(bpy) 3 , [78] Ir(dF‐CF 3 ‐ppy) 2 (dtbpy), [78] and 4‐CzIPN [79] turned on photocatalytic activity in this challenging reduction [80] .…”
Section: Resultsmentioning
confidence: 99%
“…[6,10,75] We questioned whether the structural features that render molecules effective as conventional photoredox catalysts would translate to the electron-primed photoredox manifold. [23,76,77] Intriguingly,w ef ound that electrolysis at the E red of several commonly employed photoredox catalysts Ru(bpy) 3 , [78] Ir(dF-CF 3 -ppy) 2 (dtbpy), [78] and 4-CzIPN [79] turned on photocatalytic activity in this challenging reduction. [80] While there is as ole report proposing photochemical activity of the reduced congener of an Ir-based photoredox catalyst, [81] these are the first data consistent with either Ru-based or isophthalonitrile structures acting as electron-primed photoredox catalysts.G iven that cathodic reduction of 4-CzIPN resulted in ameaningful improvement in photochemical deamination yield, we examined other isophthalonitrile catalysts.T his investigation revealed that 4-DPAIPN [82] promotes the reduction of model substrate 1 in nearly quantitative yield under electrophotocatalytic conditions.O verall, the structural diversity of the potent photocatalysts identified through these studies suggest that reductively induced photoactivity is ag eneral phenomenon and provides ac lear link between catalyst structure and reaction outcome.…”
Section: Resultsmentioning
confidence: 99%
“…One solution is to generate photoexcitable radical ions by multi‐photon processes. [3] Such photoexcited radical ions are highly oxidizing[ 3a , 3b ] or reducing species,[ 3c , 3d , 3e , 3f , 3g , 3h ] leading to a significantly expanded redox “window” for activating inert substrates. Sacrificial redox additives (e.g.…”
Section: Introductionmentioning
confidence: 99%